KEADILAN DALAM PEMBIAYAAN INFRASTRUKTUR DI INDONESIA - Ardalepa, Nurdin (IBLAM LAW REVIEW, 2023)
Infrastructure have a crucial role in the development of a country. The availability of adequate infrastructure makes it easier for the population to access their basic needs, such as highways, public transportation, clean water, and employment opportunities. In this regard, the government has been actively involved in sustainable infrastructure development, considering various aspects such as economic, social, cultural, and environmental to ensure that no aspect is neglected. Of course, such infrastructure development requires sufficient funding, one of which is through private investors, such as infrastructure financing companies. The purpose of this research is to examine the implementation of equitable infrastructure financing in Indonesia, aiming to achieve the expected outcomes of such development. The research method employed in this study is a normative juridical approach, utilizing legal regulations and a conceptual approach. The findings of this research reveal that infrastructure financing in Indonesia is not solely reliant on the national budget (APBN) but also involves private investors. The collaboration between the government and private investors in infrastructure financing is facilitated through the Public Private Partnership (PPP) scheme, with project execution under the Private Sector Participation (KPS). Furthermore, the government has introduced various policies and strategies to realize equitable infrastructure development in Indonesia.